GE_GERICHTE P/10222/2022 vom 23. Oktober 2024 - GE Cour de justice (2024)
VIOLATION DE DOMICILE;CONTRAINTE(DROIT PÉNAL);ERREUR SUR LES FAITS(DROIT PÉNAL);ERREUR DE DROIT(DROIT PÉNAL) | CP.181; CP.186; CP.13; CP.21